The Effectiveness of Gallery Walk and Simulation (GALSIM) to Improve Students’ Achievement in Fiqh Learning - Ismail, I; Anitah W, Sri; Sunardi, S; Rochsantiningsih, Dewi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
This article presents the efforts of teacher in enhancing students’ achievement through the implementation of cooperative learning model: Gallery Walk and Simulation (GALSIM). This classroom action research aims to describe the improvement of students’ achievement of Fiqh subject matter. The data was collected by observation, actions, documents, and tests. This two-cycle research used four steps i.e. planning, action, observation and reflection in each cycle. The results show that the implementation of GALSIM could improve students’ activity along the learning process. Moreover, the implementation of this model could also improve students’ achievement at the end of their study on Fiqh. Tulisan ini mengetengahkan upaya guru dalam meningkatkan prestasi siswa melalui penerapan model pembelajaran kooperatif berupa Gallery Walk dan Simulation (GALSIM). Penelitian tindakan kelas ini bertujuan untuk mendeskripsikan kemajuan prestasi siswa pada pelajaran Fikih. Data penelitian terkumpul melalui pengamatan, tindakan, dokumentasi, dan tes. Penelitian dengan dua siklus ini memanfaatkan empat langkah berupa perencanaan, tindakan, pengamatan, dan refleksi dalam setiap siklusnya. Temuan riset ini menunjukkan bahwa penerapan GALSIM dapat meningkatkan keaktifan siswa selama pembelajaran. Di samping itu, penerapan model ini dapat pula meningkatkan prestasi siswa dalam mempelajari Fikih.